Effects of docosahexaenoic acid on large-conductance Ca2+-activated K+ channels and voltage-dependent K+ channels in rat coronary artery smooth muscle cells - Lai Li-hong; Wang Ru-xing; Jiang Wen-ping; Yang Xiang-jun; Song Jian-ping; Li Xiao-rong; Tao Guo (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of docosahexaenoic acid (DHA) on large-conductance Ca2+-activated K+(BKCa) channels and voltage-dependent K+ (KV) channels in rat coronary artery smooth muscle cells (CASMCs). Methods: Rat CASMCs were isolated by an enzyme digestion method. BKCaand KV currents in individual CASMCs were recorded by the patch-clamp technique in a whole-cell configuration at room temperature. Effects of DHA on BKCa and KV channels were observed when it was applied at 10, 20, 30, 40, 50, 60, 70, and 80 μmol/L. Results: When DHA concentrations were greater than 10 μmol/L, BKCacurrents increased in a dose-dependent manner. At a testing potential of+80 mV, 6.1%±0.3%, 76.5%±3.8%, 120.6%±5.5%, 248.0%±12.3%, 348.7%±17.3%, 374.2%±18.7%, 432.2%±21.6%, and 443.1%±22.1% of BKCacurrents were increased at the above concentrations, respectively. The half-effective concentration (EC50) of DHA on BKCa currents was 37.53±1.65 μmol/L. When DHA concentrations were greater than 20 μmol/L, KV currents were gradually blocked by increasing concentrations of DHA. At a testing potential of +50 mV, 0.40%±0.02%, 1.37%±0.06%, 11.80%±0.59%, 26.50%±1.75%, 56.50%±2.89%, 73.30%±3.66%, 79.70%±3.94%, and 78.1%±3.91% of KV currents were blocked at the different concentrations listed above, respectively. The EC50 of DHA on KV currents was 44.20±0.63 μmol/L. Conclusion: DHA can activate BKCa channels and block KV channels in rat CASMCs, and the EC50 of DHA for BKCa channels is lower than that for KVchannels; these findings indicate that the vasorelaxation effects of DHA on vascular smooth muscle cells are mainly due to its activation of BKCachannels.